Economic and political dynamics in Philippine development - Alburo, Florian A. (Philippine Review of Economics, 2016)
This paper hypothesizes that the long-term political behavior of breaking the country into finer geographical and political entities has been inimical to its sustainable long-term economic growth. The splitting of provinces and creation of new ones, legislating of more congressional districts, and further breaking up of even the lowest government levels fragment markets, raise real financial and transactions costs, bloat government’s budgets and the bureaucracy, and burden the private sector. Partial evidence is explored showing this behavior in the country’s long-term development history and some policy directions are suggested.